Tlr2/4‐Mediated Hyperinflammation Promotes Cherubism‐Like Jawbone Expansion in Sh3bp2 (P416R) Knockin Mice. (30th October 2021) - Fujii, Yasuyuki; Monteiro, Nelson; Sah, Shyam Kishor; Javaheri, Homan; Ueki, Yasuyoshi; Fan, Zhichao; Reichenberger, Ernst J; Chen, I‐Ping
ABSTRACT: Cherubism (CBM), characterized by expansile jawbones with multilocular fibrocystic lesions, is caused by gain‐of‐function mutations in SH3 domain‐binding protein 2 ( SH3BP2 ; mouse orthologue Sh3bp2 ). Loss of jawbone and dental integrity significantly decrease the quality of life for affected children. Treatment for CBM is limited to multiple surgeries to correct facial deformities. Despite significant advances made with CBM knockin (KI) mouse models ( Sh3bp2 KI/KI ), the activation mechanisms of CBM lesions remain unknown because mutant mice do not spontaneously develop expansile jawbones. We hypothesize that bony inflammation of an unknown cause triggers jawbone expansion in CBM. To introduce jawbone inflammation in a spatiotemporally controlled manner, we exposed pulp of the first right mandibular molar of 6‐week‐old Sh3bp2 +/+, Sh3bp2 KI/+, and Sh3bp2 KI/KI mice. Bacterial invasion from the exposed pulp into root canals led to apical periodontitis in wild‐type and mutant mice. The pathogen‐associated molecular patterns (PAMPs)‐induced inflammation of alveolar bone resulted in jawbone expansion in Sh3bp2 KI/+ and Sh3bp2 KI/KI mice. CBM‐like lesions developed exacerbated inflammation with increased neutrophil, macrophage, and osteoclast numbers. These lesions displayed excessive neutrophil extracellular traps (NETs) compared to Sh3bp2 +/+ mice. Expression levels of IL‐1β, IL‐6, and TNF‐α were increased in periapical lesions of Sh3bp2 +/+, Sh3bp2 KI/+, and Sh3bp2 KI/KI mice and also in plasma and the left untreated mandibles (with no pulp exposure) of Sh3bp2 KI/KI mice, suggesting a systemic upregulation. Ablation of Tlr2/4 signaling or depletion of neutrophils by Ly6G antibodies ameliorated jawbone expansion induced by PAMPs in Sh3bp2 KI/KI mice. In summary, successful induction of CBM‐like lesions in jaws of CBM mice is important for studying initiating mechanisms of CBM and for testing potential therapies. Our findings further emphasize a critical role of host immunity in the development of apical periodontitis and the importance of maintaining oral health in CBM patients. © 2021 The Authors. JBMR Plus published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research.